Evaluation of Bawaslu Sidoarjo’s Recommendatory Authority inHandling Village Head Neutrality Violations in the Perspective ofBridgman and Davis Theory - Nur Aini Fatjeriyah; Muhammad Agus Muljanto (Lavish Opulent Education, 2026)
This research evaluates the recommendatory authority of the SidoarjoRegency Election Supervisory Body (Bawaslu) in addressing neutralityviolations involving twelve village heads in Buduran District during the 2024General Election. While Bawaslu procedurally performed its functions withprofessional rigor, a significant asymmetry exists between the burden ofmaterial evidence and the restrictive nature of sanctioning enforcement.Grounded in the policy evaluation framework of Bridgman and Davis (2000),comprising input, process, output, and outcome indicators. This descriptivequalitative study identifies a